Phytoplankton diversity and their relationship with water quality parameters in the middle basin of Ogun River, Abeokuta, Southwest Nigeria - Amoda, Oyefolake; Abiodun, Odunayo; Adewale, Caleb (Acta Agraria Debreceniensis, 2025)
Phytoplankton are crucial bioindicators for assessing freshwater ecosystem health. This study investigates the diversity and distribution of phytoplankton and key water quality parameters in the Ogun River. Monthly samples were collected from three sites along the river between February and August 2024. Phytoplankton samples were preserved with 4% formalin and analyzed microscopically, while water quality parameters, including temperature, pH, dissolved oxygen, conductivity, transparency, total dissolved solids, nitrate, phosphate, alkalinity, and hardness, were measured using standard methods. Results showed temperature ranged from 27.3–31.9 °C, pH from 6.7–9.4, dissolved oxygen from 4.3–7.2 mgL-1, conductivity from 10.8–20.9 µS/cm, transparency from 0.27–1 m, and other parameters within specified ranges. Sixteen phytoplankton species from 10 families were identified, with the Bacillariophyceae family being the most dominant, representing 7 species. Lyngbya spp. was the most abundant species, followed by Pediastrum simplex. Species richness was 12 species at Site A, 13 at Site B, and 14 at Site C. Dominance values were 0.13, 0.11, and 0.12, respectively. Simpson’s diversity index ranged from 0.87 to 0.89, and the Shannon-Weiner index was 2.24 at Site A, 2.38 at Site B, and 2.35 at Site C. One-way ANOVA tests showed no statistically significant differences in diversity indices among the three sampling sites (p > 0.05), indicating relatively consistent phytoplankton diversity across the study area. These findings highlight the importance of integrated biological and physicochemical monitoring for effective water management and ecosystem conservation in the Ogun River.